International review of research in mental retardation. - Glidden, Laraine Masters, 1943-; Seltzer, Marsha Mailick (Academic, 2009)
International Review of Research in Mental Retardation is an ongoing scholarly look at research into the causes, effects, classification systems, syndromes, etc. of mental retardation. Contributors come from wide-ranging perspectives, including genetics, psychology, education, and other health and behavioral sciences. Volume 37 of the series focuses mainly on topics relating to parenting and families, including chapters on biomarkers in the study of families of individuals with developmental disabilities, contrasts in parenting across early school age children with developmental delays, parental contributions to communication development, and siblings of individuals with intellectual disabilities. * Provides the most recent scholarly research in the study of mental retardation * A vast range of perspectives is offered, and many topics are covered * An excellent resource for academic researchers.